Commitment among Senior Managers to the Use of District Health Information Management System 2 Data for Decision Making in Maternal and Neonatal Health in Greater Accra Region - Effah, F.D. (University of Ghana, 2019)
Background: Many countries consistently have data that is of poor quality and or data that arrives too late to back important indicators of human lives. Studies show that the standard procedure for data use to keep track and measure the health system in Sub-Saharan Africa has mostly been strictly communication reliant on, with problems due to poor response coils. Objective: To determine factors that contribute to the commitment level among senior managers toward the use of district health information management system 2 (DHIMS2) data for decisionmaking relating to maternal and neonatal health in the Tema Metropolitan Assembly area of the Greater Accra Region. Methods: This study adopted a quantitative research approach and was conducted in public health facilities in the Tema Metropolitan Assembly locale. A structured questionnaire was administered to sixty-six senior managers of health care services to collect data for the study. They responded to questions covering variables such as behavioural factors, organisational factors, and challengesassociated with commitment to using district health information management system 2 (DHIMS2) data for decision making relating to maternal and neonatal health.Socio-demographic characteristics were also analysed.Analysis of research data was done using the descriptive and inferential approach using STATA 14 and Microsoft Excel version 2016.The research hypotheses were tested using linear multiple regression analysis and correlation analysis. Results: The study revealed that the Tema Metropolitan Assembly area of the Greater Accra Region was mostly dominated by senior managers who happened to be males (67%) in the health sector. The average age distribution of senior managers within the region was 47 (38%) years with the highest age range of 51-60 (47%) recorded. The study found a significant value of p<0.021, which was less than a 0.05 level of significance. This implies that, there was no significant relationship between socio-demographic characteristics and senior managers’ commitment to data utilization for decisions on maternal and neonatal health. In addition, the study recorded a Pearson Chi-Square value of 4.001 with a respective significant value of 0.06, which was greater than a significance level of 0.05. Therefore, there was a sufficient evidence to support the claim that senior managers’ commitment was influenced by the behavioural factors on DHIMS2 data usage. The study found a Pearson Chi-Square value of 3.273 with a respective significant value of 0.070. Therefore, there was sufficient evidence to support the claim that senior managers’ commitment was influenced by the organisational factors in data usage. The study showed a significant value of .014 (p = .014), which was below 0.01. Consequently, there was a relationship in the mean of thchallenges associated with senior managers’ commitment to usage of DHIMS2 data for decision making on maternal and neonatal health. Conclusions/Recommendation: Based on the above findings the study concludes and recommends that there is the need for: intensification of community health education and mobilization on maternal and neonatal health by using the district health information management system 2 (DHIMS2) data to identify zones or areas within the community that are prone to maternal and neonatal morbidity and mortality; and senior managers’ empowerment to make decisions on maternal and neonatal health using the (DHIMS2) data is of paramount interest.With the adaptation of the district health information management system 2 (DHIMS2) data, senior managers must take keen interest in establishing or developing appropriate criteria for selecting interventions for addressing maternal and neonatal constraints. Resources should be provided to senior managers to help facilitate data gathering processes to gathering processes to find the root causes of constraints associated with maternal and neonatal health.
MPH.
Keywords: Health Information Management System; Neonatal Health; Maternal Health; Greater Accra Region